Pengaruh Penggunaan Software Geometer Sketchpad V4 Terhadap Kemampuan Pemahaman Konsep Bangun Datar - Amir, Almira (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
The background of the research is students’ comprehension of two dimentional figure was low. It caused learning meadia that used by teacher was less varied and it cannot attract students’ attention in learning. So, students’ have difficulties to retell a concept that they have learned with classified characteristic of plane figure, determine circumference and area of plane figure. The purpose of this research was conducted to know the effect of using Software Geometer Sketchpad V4 toward students’ figure concept comprehension at VII class of SMP Negeri 11 Padangsidimpuan.The theories that used in this research is Bruner Theory about the important of comprehension about the best way for student’s to learning concepts or in mathematics principle was constructed a representation from the concepts itself, and Ausubel theory is about learning meaning concepts.This research is quantitative research with experiment method used Pretest-Posttest Control Group Desain. The population in this research is students at VII Class SMP Negeri 11 Padangsidimpuan that has total class is 3 class, with 70 students. The researcher taken the sample used cluster random sampling techniqueis 43 students. Sample in experiment class that give treated are 23 students and control class that untreated are 23 students. Data processing and data analysis is done with used formula Uji t.Based on normality test and homogeneity test from the both of classes were normally distributed and homogeneous. The Test of t-test is obtained from the result of hypotheses that show Tcount = 3,603 Ttable = 2,015, so Ho was rejected and Ha was be ajjected. It concluded there is a significant effect of software geometer sketchpad V4 toward students’ two dimentional figure comprehension concept at VII Class of SMP NegeriPadangsidimpuan.